Weaving the past and present in steampunk - Lukášková, Lucie (Univerzita Pardubice, 2023)
This bachelor thesis focuses on the 20th and 21st century issues in the context of alternate history in Cherie Priest's series of novels in The Clockwork Century. The thesis outlines relevant literary and historical contexts, particularly the zombie genre, alternate history, Russian America, The Civil War, and the Klondike Gold Rush. Additionally, the thesis analyzes the selected series of novels and explores the issues of feminism, poverty, pollution, and biological weaponry.
Keywords: steampunk; znečištění planety; třídní diskriminace; feminismus; Mechanické století; zombies; alternativní historie; technologie; Americká občanská válka; biologické zbraně; Cherie Priest; Zeměstřas; Bitevník; Ganymédes; Nepopsatelní; Fiddlehead; Jacaranda; Steampunk; pollution; classism; feminism; Clockwork Century; zombies; alternate history; technology; American Civil War; biological weapons; Cherie Priest; Boneshaker; Dreadnought; Ganymede; Inexplicables; Fiddlehead; Jacaranda